Quality Changes in Traditionally Dried and Smoked Sarangi Fish (Salmophasia bacaila) Stored at Ambient and Refrigerated Temperature - Jakhar, J. K.; Sagar, Mrinalni; Sengar, N. S.; Sahu, Parmeshwari; Sahu, Vriddhi; Dhruve, Domendra; Gendley, M. K.; Jakhar, Sunita; Ngasotter, Soibam (International Journal of Bio-resource and Stress Management, 2025)
The study was conducted during March to April, 2025 at the Department of Fish Harvest and Post-Harvest Technology, LSPN College of Fisheries, Dau Shri Vasudev Chandrakar Kamdhenu Vishwavidyalaya, Kawardha, Chhattisgarh, India to investigate the quality changes in traditionally dried and smoked Sarangi fish (Salmophasia bacaila) during 30 days of storage under ambient and refrigerated conditions. Key parameters, including proximate composition, biochemical indices (TVB-N, peroxide value, free fatty acid), microbial load (total plate count), and sensory attributes, were assessed at regular intervals to evaluate the impact of storage environment and processing method on product stability. Results showed a progressive decline in protein and lipid content over time, with more pronounced reductions under ambient storage. Biochemical indicators such as total volatile base nitrogen (TVBN), peroxide value (PV), and free fatty acids (FFA) increased significantly, particularly at ambient temperatures, indicating spoilage and oxidative degradation. Total plate count (TPC) also increased over the storage period, with smoked samples showing higher microbial proliferation than dried samples, especially under non-refrigerated conditions. Sensory evaluation revealed a decline in consumer acceptability in terms of appearance, aroma, texture, and taste, more so in samples stored at ambient temperature. Overall, dried Sarangi exhibited better stability compared to smoked samples, and refrigeration effectively mitigated quality deterioration across all parameters. These findings highlighted the importance of proper storage and processing techniques in maintaining the safety, nutritional value, and sensory quality of traditionally processed fish products.